INSIGHTS INTO THE ROLE OF MORUS ALBA IN REVERSING OBESITY-ASSOCIATED HEPATIC STEATOSIS AND RELATED METABOLIC DISORDER IN RATS - Metwally, Fatehya M; Ahmed, Hanaa H; Rashad, Hend; Zaazaa, Asmaa M (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The goal of the present study was to examine the viability of Morus alba (M. alba) ethanolic extract in repression of obesity-associated hepatic steatosis and related metabolic disorder; dyslipidemia, hyperinsulinemia, and glycemic status. Methods: Adult female albino rats were randomly assigned into four groups, eight rats each as follows: Group (1) control group received standard rodent diet for 24 weeks. The other three groups administered high cholesterol diet for 12 weeks and served as obese group, M. alba-treated group, and simvastatin-treated group. Results: The current results showed an increment in thoracic circumference (TCX) and abdominal circumferences (AC) as well as body mass index (BMI) in obese group. In addition, dyslipidemia, hyperinsulinemia, hyperglycemia, and insulin resistance have been elucidated in obese group. Moreover, hepatic malondialdehyde (MDA), nitric oxide (NO), serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), and bilirubin values were significantly increased in obese groups versus control group. On the other hand, administration of ethanolic extract of Morus alba or simvastatin could significantly lessen BMI and in addition to improve dyslipidemia in obese group. Glucose, insulin levels, and insulin resistance value in serum samples demonstrated a significant reduction in obese group upon treatment with M. alba ethanolic extract or simvastatin. Furthermore, noticeable depletion in hepatic MDA, NO contents, serum ALT, AST activities, and serum bilirubin level was recorded as a result of treatment with either ethanolic extract of M. alba or simvastatin. Histopathological examination of liver tissue showed ballooning degeneration in the hepatocytes (hepatic steatosis) associated with inflammatory cells penetration in portal zone in obese group. Meanwhile, the treatment of obese groups with ethanolic extract of M. alba or simvastatin was found to restore the structural organization of the liver. Conclusion: The present findings provide a novel aspect for understanding of the role of M. alba against obesity-associated liver diseases and related metabolic disorder. The mechanisms underlying these effects seem to depend on the hypolipidemic potential, anti-inflammatory property, and antioxidant activity of its phytochemicals. Keywords: Obesity, Morus alba, Dyslipidemia, Hyperinsulinemia, Hyperglycemia, Hepatic steatosis.